2018
DOI: 10.1038/s41598-018-34321-x
|View full text |Cite
|
Sign up to set email alerts
|

Fearful dogs have increased plasma glutamine and γ-glutamyl glutamine

Abstract: Anxiety-related disorders, including fearfulness are common and leading welfare problems among the worldwide dog population. The etiology of anxieties is complex and affected by genetic and environmental factors. Thus, there is a need for more comprehensive approaches, such as metabolomics, to understand the causes of anxiety and to identify anxiety-related biomarkers for more efficient diagnostic and treatment options. To study metabolic alterations related to canine fearfulness, a non-targeted plasma metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 75 publications
0
20
0
Order By: Relevance
“…Thus, more research is needed to investigate what amount of exercise is beneficial for protecting dogs against non-social fear. Recent studies have also revealed increased levels of stress-related biomarkers in fearful dogs 38,39 . On the other hand, earlier studies have shown that fearful dogs have difficulty in solving cognitive tasks and show more stress-related behaviour when solving the puzzle 57,58 , suggesting that fearful dogs are not ideal partners for training.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, more research is needed to investigate what amount of exercise is beneficial for protecting dogs against non-social fear. Recent studies have also revealed increased levels of stress-related biomarkers in fearful dogs 38,39 . On the other hand, earlier studies have shown that fearful dogs have difficulty in solving cognitive tasks and show more stress-related behaviour when solving the puzzle 57,58 , suggesting that fearful dogs are not ideal partners for training.…”
Section: Discussionmentioning
confidence: 99%
“…We recently reported novel loci for canine fearfulness and noise sensitivity 14 . In addition, we have previously reported changes such as increased plasma glutamine levels in fearful dogs 16,17 . Candidate loci and genes have also been reported for example for canine fear and aggression 18 , social behaviour 19,20 , and obsessivecompulsive disorder 21,22 .…”
Section: Introductionmentioning
confidence: 94%
“…These studies point to the role of oxidative stress, alterations in AA and energy metabolism (i.e., mitochondrial regulation) and neurotransmission [35,36]. Glutamine, γ-glutamyl-glutamine Glutamine metabolism [38] Recently, metabolomics approaches were also conducted on fearful dogs (Table 2). Compared to classical rodent models, dogs share comparable lifestyle and environmental factors like humans and are even genetically and physiologically closer to humans [38].…”
Section: Metabolomics In Anxiety Modelsmentioning
confidence: 99%
“…Glutamine, γ-glutamyl-glutamine Glutamine metabolism [38] Recently, metabolomics approaches were also conducted on fearful dogs (Table 2). Compared to classical rodent models, dogs share comparable lifestyle and environmental factors like humans and are even genetically and physiologically closer to humans [38]. The study revealed changes in glutamine metabolism (i.e., higher plasma glutamine and γ-glutamyl-glutamine levels in fearful vs. non-fearful dogs).…”
Section: Metabolomics In Anxiety Modelsmentioning
confidence: 99%
See 1 more Smart Citation